EXPERIMENTAL STAND AND METHODOLOGY FOR THE ROLLER’S WORKING BODY RESEARCH - O. Y. Kazakov; G. V. Kustarev (Вестник СибАДИ)
Introduction. The paper researches the sphere of paving with a roller. The authors describe the current situation in the asphalt concrete’s application as a road surface. Moreover, the authors conduct the excursion into the history of material. The paper presents the preconditions that justify the need for creating recommendations, schemes and methods for experimental study of the working body and material under laboratory conditions of various kinds. The aim of the study is to create the stand concept and methods for experimental research of the roller’s working body in the laboratory.Materials and methods. The paper described a laboratory stand for experiments in the sphere of roller’s working equipment. The authors demonstrated the construction made of a base, a stiffener box, guides and a movable part with a frame and equipment, suspended above the compacted material’s container.Results. As a result, the authors presented the detailed methodology for conducting experiments and recommendations for its transformation in the considered sphere. The paper showed all the necessary data for the design, construction of the test bench and experiments with the roller’s working equipment. Discussion and conclusions. Researchers, especially beginners, receive an additional tool for study of dependencies and phenomena that occur during compaction of material by the roller. Therefore, the authors develops the scheme for the research of the roller’s working body in small area conditions and in extensive laboratories.